Bioprocessing of Plant in Vitro Systems 2016
DOI: 10.1007/978-3-319-32004-5_15-1
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Transformations of Plant Secondary Metabolites

Abstract: The aim of this chapter is to present the authors' view on the place and role of microbial transformation reactions as a perspective means of processing of plantderived biologically active compounds into metabolites with new and/or increased activity and availability and decreased toxicity. Some microbial transformations providing information regarding metabolism in humans and mammals of plant-derived secondary metabolites applied as drugs and/or food additives are also considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 199 publications
(233 reference statements)
0
4
0
Order By: Relevance
“…Fungi can biotransform terpenoids in particular product(s) and at specific rate(s) through multiple reactions strongly influenced by the cultivation conditions (Frija et al, 2011; Ghasemi et al, 2014; Mutafova et al, 2016). However, production yields of each distinct product from a stereo-selective hydroxylation of the terpenoid are usually very low (2–20%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fungi can biotransform terpenoids in particular product(s) and at specific rate(s) through multiple reactions strongly influenced by the cultivation conditions (Frija et al, 2011; Ghasemi et al, 2014; Mutafova et al, 2016). However, production yields of each distinct product from a stereo-selective hydroxylation of the terpenoid are usually very low (2–20%).…”
Section: Discussionmentioning
confidence: 99%
“…In most studies reported so far, the terpenoid containing medium is inoculated with mycelia (previously grown in a standard growth medium) and agitated batch or fed-batch cultivation conditions are used (Frija et al, 2011; Schrader and Bohlmann, 2015; Mutafova et al, 2016). Terpenoids are known to play major roles in plant defense mechanisms (Gershenzon and Dudareva, 2007; Mutafova et al, 2016), probably explaining why the LA plant extract inhibited the germination of P. janczewskii conidia in the agitated cultures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations